Makna Tradisi Uang Panai’ Bagi Masyarakat Bugis Tolitoli - Falah, Ali Akbarul; Achmad, Mukhsin (Indonesian Journal of Islamic Education and Local Culture, 2024)
This study explains the tradition of Uang Panai’ in the Bugis Tolitoli community, located in the Tolitoli Regency. It also explores how the people of Tolitoli perceive the significance of the Uang Panai’ cultural practice. This study aims to learn more about the practice and meaning of Uang Panai’ for the Bugis Tolitoli community. This research uses ethnographic research methods with a qualitative approach by describing the research objectives. Researchers found that Uang Panai’ for the Bugis Tolitoli community must be held as a tribute to the bride and ease the burden on the woman's family, as well as to provide prestige for the family holding the wedding, behind the obligation to fulfil the Uang Panai’ accompanied by the awareness of both parties of the prospective bride to determine the value of Uang Panai’ according to the ability of the male party.